Single Image Capture of Bioactive Ion Crosstalk within Inter‐Organelle Membrane Contacts at Nanometer Resolution. Issue 8 (1st July 2022) - Fang, Guiqian; Chen, Huimin; Shao, Xintian; Wang, Han; Zhan, Dongxue; Wang, Ran; Meng, Peng; Fang, Hongbao; Liu, Fei; Ling, Peixue; Wu, Zhongyu; Diao, Jiajie; et al.
Abstract: Rapid bioactive ion exchange is a form of communication that regulates a wide range of biological processes. Despite advances in super‐resolution optical microscopy, visualizing ion exchange remains challenging due to the extremely fast nature of these events. Here, a "converting a dynamic event into a static image construction" (CDtSC) strategy is developed that uses the color transformation of a single dichromatic molecular probe to visualize bioactive ion inter‐organelle exchange in live cells. As a proof of concept, a reactive sulfur species (RSS) is analyzed at the mitochondria‐lysosome contact sites (MLCs). A non‐toxic and sensitive probe based on coumarin‐hemicyanine structure is designed that responds to RSS localized in both mitochondria and lysosomes while fluorescing different colors. Using this probe, RSS give‐and‐take at MLCs is visualized, thus providing the first evidence that RSS is involved in inter‐organelle contacts and communication. Taken together, the CDtSC provides a strategy to visualize and analyze rapid inter‐organelle ion exchange events in live cells at nanometer resolution. Abstract : A "converting a dynamic event into a static image construction" strategy is developed, which combines innovation in optical microscopy with unique dichromatic molecular probe design to visualize bioactive ion exchange.